STRATEGI PENINGKATAN INCOME DI D’SRUPUT DENGAN MENGGUNAKAN MENU ENGINEERING - Wulandari, Rizky; Asnur, Lise (Journal of Food Technology and Agroindustry dipublikasikan oleh Universitas Wiraraja, 2024)
This research is motivated by the problems found in D’Sruput, where are drinks that have low popularity and low profitability so that the income generated is not optimal. The purpose of this study is to analyze the income increasing strategi at D’Sruput by looking atthe level of popularity and profitability of each drink. The method in this study uses a qualitative descriptive method , in which the data obtained will be processed using menu engineering with the help of Microsoft excel with beverage sales history data obtained from October 2022 - Desember2022. Based on the results of research conducted by the autor using the menu engineering method. strategies for increasing income can be determined in the from of : maintaining quality for the star category, reducting beverage costs for the plowhors category, adding or reducting recipes or making changes to products for the puzzle category and changing the menu for the dog category